2017
DOI: 10.1111/1751-7915.12706
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of LotP from Liberibacter asiaticus

Abstract: Summary Liberibacter asiaticus is an unculturable parasitic bacterium of the alphaproteobacteria group hosted by both citrus plants and a psyllid insect vector (Diaphorina citri). In the citrus tree, the bacteria thrive only inside the phloem, causing a systemically incurable and deadly plant disease named citrus greening or Huanglongbing. Currently, all commercial citrus cultivars in production are susceptible to L. asiaticus, representing a serious threat to the citrus industry worldwide. The technical inabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…This protein was previously misannotated as an LA1 aminopeptidase, but structural analysis suggested that LotP actually belongs to a different, uncharacterized family of proteins. Co-immunoprecipitation assays identified GroEL as the main interacting protein, and a physical interaction between GroEL and LotP was confirmed via two-hybrid assay [Loto et al, 2017]. LotP is predicted to be critical to the pathogenesis in planta through this GroEL interaction and may have a role in masking Gro-EL from the plant immune defense system.…”
Section: Salicylic Acid Hydroxylase (Saha)mentioning
confidence: 83%
See 3 more Smart Citations
“…This protein was previously misannotated as an LA1 aminopeptidase, but structural analysis suggested that LotP actually belongs to a different, uncharacterized family of proteins. Co-immunoprecipitation assays identified GroEL as the main interacting protein, and a physical interaction between GroEL and LotP was confirmed via two-hybrid assay [Loto et al, 2017]. LotP is predicted to be critical to the pathogenesis in planta through this GroEL interaction and may have a role in masking Gro-EL from the plant immune defense system.…”
Section: Salicylic Acid Hydroxylase (Saha)mentioning
confidence: 83%
“…Further, J Mol Microbiol Biotechnol 2018;28:116-127 DOI: 10.1159/000492386 to determine its biological significance. In silico analysis of LotP revealed that the sequence is highly conserved among the Rhizobiaceae family (56-86% identity), and it is vastly distributed in α-proteobacteria (35% plant-associated bacteria, 1/2 of these are plant pathogens) [Loto et al, 2017]. This protein was previously misannotated as an LA1 aminopeptidase, but structural analysis suggested that LotP actually belongs to a different, uncharacterized family of proteins.…”
Section: Salicylic Acid Hydroxylase (Saha)mentioning
confidence: 99%
See 2 more Smart Citations
“…The genome-enabled ability to analyze CLas gene expression in the plant and vector led to the identification of gene activation patterns and regulatory elements in the bacterium . A LuxR receptor of an unknown citrus signal increased CLas symptoms in transgenic citrus (Gabriel, 2017), and the LdtR transcriptional regulator was shown to be a master regulator of global gene expression, including that of the stress response gene LotP (Pagliai et al, , 2017Loto et al, 2017). The genome also revealed that CLas likely has a functional Sec (Type II) secretion system for transporting proteins from the bacterial cell to the extracellular environment.…”
Section: Functional Comparative Genomics and The Identification Of Inmentioning
confidence: 99%